SISTEM SOSIAL-BUDAYA PANTAI: Mata Pencaharian Nelayan dan Pengolah Ikan di Kelurahan Panggung Kecamatan Tegal Timur Kota Tegal - Shinta Septiana (Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
Panggung is located in Tegal City, a coastal village whose heterogeneous social structure, with a high work ethic, strong social solidarity, open to change and with closed social interactions. The livelihood system of this community is heterogeneous which evolve from traditional to modern types of work, including traditional fishing by local fishermen and fish processed food for commercial purpose by local house wives. Fishermen and local families not only sell raw fish but also produce a household scale of processed products so that the local livelihood system experiences and develops not only traditional fishing but also the business of processed fish products of household scale.